2009
DOI: 10.1111/j.1755-5922.2009.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Cilnidipine: A New Generation Ca2+ Channel Blocker with Inhibitory Action on Sympathetic Neurotransmitter Release

Abstract: Cilnidipine is a unique Ca2+ channel blocker with an inhibitory action on the sympathetic N‐type Ca2+ channels, which is used for patients with hypertension in Japan. Cilnidipine has been clarified to exert antisympathetic actions in various examinations from cell to human levels, in contrast to classical Ca2+ channel blockers. Furthermore, renoprotective and neuroprotective effects as well as cardioprotective action of cilnidipine have been demonstrated in clinical practice or animal examinations. After the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 125 publications
(144 reference statements)
3
66
0
2
Order By: Relevance
“…14,15 Cilnidipine, a new type of CCB that blocks the N-type calcium channel and the L-type calcium channel, is therefore thought to affect bone metabolism, possibly through the inhibition of both the sympathetic nervous system and the voltage-dependent calcium channel. [16][17][18][19] b-blockers are known to affect the relationship between the sympathetic nervous system and bone metabolism, leading to increased BMD. 20,21 Thus, in this study, we investigated the effects of cilnidipine on bone metabolism in comparison with those of amlodipine, an L-type dihydropyridine CCB, and carvedilol, a b-blocker that is known to reduce fracture risk though the inhibition of osteoclast activation via b2-adrenergic receptors, in an ovariectomy-induced rat osteoporosis model.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Cilnidipine, a new type of CCB that blocks the N-type calcium channel and the L-type calcium channel, is therefore thought to affect bone metabolism, possibly through the inhibition of both the sympathetic nervous system and the voltage-dependent calcium channel. [16][17][18][19] b-blockers are known to affect the relationship between the sympathetic nervous system and bone metabolism, leading to increased BMD. 20,21 Thus, in this study, we investigated the effects of cilnidipine on bone metabolism in comparison with those of amlodipine, an L-type dihydropyridine CCB, and carvedilol, a b-blocker that is known to reduce fracture risk though the inhibition of osteoclast activation via b2-adrenergic receptors, in an ovariectomy-induced rat osteoporosis model.…”
Section: Introductionmentioning
confidence: 99%
“…10 Meanwhile, previous studies have revealed that cilnidipine, an N-type and L-type CCB, is capable of blocking the two types of channels. 11 N-type calcium channels are members of the major calcium channel family, but they are fundamentally different from the other calcium channels and have highly distinctive calcium-regulation mechanisms. 12,13 N-type calcium channels are heteromultimeric complexes consisting of a pore-forming a1 subunit (a1B) and at least two auxiliary subunits, b and a2d, which modulate the function of the a1 subunit.…”
Section: Introductionmentioning
confidence: 99%
“…11, 12 Abe conducted a study to compare the effect of cilnidipine against those of Amlodipine on BP, albuminuria. In hypertensive patients with mild to moderate chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%